Actions of angiotensin II and dopamine in the medial preoptic area on prolactin secretion - Leite, C. M. (2008)
Dopamine (DA) is known as a primary regulator of prolactin secretion (PRL) and angiotensin II (Ang II) has been recognized as one brain inhibitory factor of this secretion. In this work, estrogen-primed or unprimed ovariectomized rats were submitted to the microinjection of saline or Ang II after previous microinjection of saline or of DA antagonist (haloperidol, sulpiride or SCH) both in the medial preoptic area (MPOA). Our study of these interactions has shown that 1) estrogen-induced PRL secretion is mediated by Ang II and DA actions in the MPOA, i.e. very high plasma PRL would be prevented by inhibitory action of Ang II, while very low levels would be prevented in part by stimulatory action of DA through D2 receptors, 2) the inhibitory action of Ang II depends on estrogen and is mediated in part by inhibitory action of DA through D1 receptors and in other part by inhibition of stimulatory action of DA through D2 receptors. © 2008 Institute of Physiology v.v.i., Academy of Sciences of the Czech Republic.